The uses and functions of mew in mapudungun - Harmelink, Bryan L. (Lenguas Modernas, 2017)
Augusta’s Gramática Araucana (1903: 128) and Moesbach’s ldioma Mopuche (1963: 170) both note the "vague" meaning of mew in Mapudungun. The wide range of semantic Notions associated with new creates difficulties in its analysis and also is a source of potential interference in the acquisition of Spanish by dominant Mapudungun speakers. In this study, examples of the diverse uses of new establish its function as a post-position and demonstrate that the meaning of new cannot be determined without context. ’Point of reference’ is proposed as a definition for mew, being a shared component of meaning in the different uses of new